Spotify WOM by Millennial Generation - Amanda, Rissa (Jurnal Komunikasi, 2022)
The presence of Spotify as an online music streaming platform is a new alternative for music lovers to enjoy music without having to buy physical albums or download songs illegally and stored it on smartphones, which take a lot of memory. Spotify is getting more and more popular as we can see from the increasing number of Spotify users every year. Therefore, this study wants to know in depth how the millennial generation's experience in using Spotify can influence their decision in recommending online music streaming to non-Spotify users with the WOM technique. This is because Spotify is one of the most popular online music streaming platforms. This research using phenomenology method that is equipped with in-depth interviews. The results of the study show that millennial Spotify users are satisfied with the quality and the many benefits they get, especially if they choose the premium service. So they want to recommend this application to music lovers, especially music streaming lovers. Spotify is also very suitable for music lovers who are active, productive, and often listen to the songs.